Taxonomy and redescription of the Atherton Antechinus, Antechinus godmani (Thomas) (Marsupialia: Dasyuridae) - Baker, Andrew M; Dyck, Steve Van (Zootaxa, 2013)
We provide a taxonomic redescription of the dasyurid marsupial Atherton Antechinus, Antechinus godmani (Thomas). A. godmani is only rarely encountered and limited to wet tropical rainforests of north-east Queensland, Australia, between the towns of Cardwell and Cairns (a distribution spanning 135 kilometres from north to south). The distinctive species occurs at altitudes of over 600 meters asl, in all major rainforest types, and can be found with both the northern subspecies of the Yellow-footed Antechinus, A. flavipes rubeculus Van Dyck and the Rusty Antechinus, A. adustus (Thomas). A. god-mani is clearly separated from all congeners on the basis of both morphometrics and genetics. A. godmani can be distin-guished from all extant congeners based on external morphology by a combination of large size, naked-looking tail and reddish fur on the face and head. A. godmani skulls are characteristically large, with a suite of long features: basicranium, palate, upper premolar tooth row, inter-palatal vacuity distance and dentary. Phylogenies generated from mt- and nDNA data position Antechinus godmani as monophyletic with respect to other members of the genus; A. godmani is strongly supported as the sister-group to a clade containing all other antechinus, but excluding the south-east Australian Dusky An-techinus, A. swainsonii (Waterhouse) and Swamp Antechinus, A. minimus (Geoffroy). Antechinus godmani are genetically very divergent compared to all congeners (mtDNA: range 12.9–16.3%).